Clinical treatment and prognosis of equine odontoclastic tooth resorption and hypercementosis. (3rd April 2015) - Lorello, O.; Foster, D. L.; Levine, D. G.; Boyle, A.; Engiles, J.; Orsini, J. A.
Summary: Reasons for performing study: Equine odontoclastic tooth resorption and hypercementosis is an infrequent and underdiagnosed form of severe dental disease in horses that can affect quality of life. The study was performed to compare the clinical, radiographic, histological and prognostic findings specific to equine odontoclastic tooth resorption and hypercementosis in horses. Removal of affected teeth is currently the best treatment. Objectives: The goals are to report salient clinical and histological features of the disease and its management in a case series describing an under‐reported syndrome in horses and the long‐term prognosis. Study design: Retrospective case series. Methods: Medical records from New Bolton Center, University of Pennsylvania from January 2000 to December 2012 were reviewed from horses that had a diagnosis of 'cementoma' or 'hypercementosis' and any associated dental‐related diagnosis affecting the teeth and oral cavity. Radiographic, surgical and histological reports were collated and the clinical cases compared and tabulated to provide a better description of the equine disease. Results: A total of 18 cases were identified, 17 of which were geldings and one of which was a nonbreeding stallion; no mares had the disease. The mean age at diagnosis was 24 years, with a range of 17–29 years. There was no breed predilection, and varied clinical signs relating to the mouth were found. Some teeth involved had only radiographic changes of disease and not gross clinical evidence. The mandibular incisors were generally affected earlier than the maxillary incisors, but the disease is progressive, and eventually, all of the incisors and sometimes the canines are involved. No premolars or molars were affected in this case series. Conclusions: Based on this case series, all teeth, and particularly the incisors, should be examined for signs of gingivitis and hypercementosis and subsequently radiographed for an early diagnosis and management. When compared with our hospital population, older geldings were more likely to be affected with cementoma formation and its accompanying resorptive process. Removal of clinically and radiographically affected teeth carries a good prognosis for improved quality of life.